A construal level analysis of organizational change processes. (2021) - Berson, Yair; Oreg, Shaul; Wiesenfeld, Batia
Abstract: To effectively manage planned change and understand differences in leaders' and recipients' responses to it, it is essential to understand how change is cognitively represented by organization members. In this theory-development article, we draw upon construal-level theory (CLT) and conceptually explore the role of change construal level in explaining responses to organizational change. We discuss differences between change leaders' and recipients' change construals, and differences in the relationships between change construal level and the response to change as a function of the change activities taking place. Specifically, we argue that high-level (i.e., abstract) construals of change will facilitate the effective initiation of change when the focus is on equilibrium-breaking activities, and that low-level (i.e., concrete) construals will facilitate the effective implementation of change when the focus is on institutionalization of the change. We further propose that leaders' engagement in visionary leadership increases the likelihood that their generally higher level construal of change will be integrated into recipients' change construals, elaborating and elevating them, and that recipients' engagement in upward prohibitive voice behaviors will increase the likelihood that their generally lower construal of change will be integrated into leaders' change construals, elaborating and concretizing them. We discuss theoretical and practical implications of our framework.